(untitled) (Journal of history, 2021)
The article examines the cult-ritual or cult-memorial objects known in science as barrows with “mustaches”, which are still mysterious both in their origin and in content, as well as in their functional purpose. In general, the content and nature of the events that unfolded on the area of these objects are not entirely known, since so far the researchers do not have sufficient materialized remains, which give rise to various hypothetical conclusions and guesses, starting from a purely pragmatic approach in order to save time and labor costs. ending with the act of recoding the originally laid down semantic load in order to adapt it to their mythological complexes. In addition, the issues of chronological attribution of this type of archaeological monuments and the need to return to the issue of their comprehensive study at an interdisciplinary level are touched upon. According to the author, the latter circumstance will allow, first of all, to determine the dates of specific objects, and in some cases the stages of construction of various components of the entire ensemble, since there are opinions about the simultaneity of individual components – a large mound and small objects, the whiskers themselves, which could be attached later to early burial (or memorial) structures. The author proposes to consider in the future “barrows with mustaches”, geoglyphs and arans, as similar in content semantics load, one-order phenomena that took place in the steppe space in the 2nd-5th centuries. Key words: burial mounds with “ridges”, cultural and chronological affiliation, Hunnic time, pre- Türks, semantic meaning.